Polyurethane free biobased epoxy binder for cork agglomeration - Quinquet, Lucie; Vincent, Luc; Guigo, Nathanaël; Sbirrazzuoli, Nicolas (Industrial crops and products, 2025)
Given the increasing need for sustainable and environmentally friendly materials, addressing the limitations of traditional cork agglomeration processes is crucial. Cork, a material widely used in an agglomerated form, usually includes the use of polyurethane in the agglomeration process, which can cause toxicity and environmental issues. In this work, a biobased, non-toxic epoxy resin was developed, and cork agglomerates were created with the aim to replace polyurethane in cork stoppers and decorative or insulation panels. The mechanical properties of the agglomerates were studied using tensile testing and dynamical mechanical analysis (DMA). The interactions with solvents were followed using contact angle and by determining the solvent absorption rates. The thermal degradation of the samples was followed using thermogravimetric analysis (TGA) and degradation kinetics. Finally, the samples were compared with an analogue sample agglomerated using a typical polyurethane binder and showed higher resistance to solvent absorption and to thermal degradation. Scanning electron microscopy (SEM) exhibited similarities for both samples. The mechanical properties of the samples were compared, showing that the biobased sample was more elastic, stiffer, tougher and could withstand more stress before breaking, showing overall promising results. [Display omitted] •Cork can be agglomerated with a Epoxidized linseed oil/tartaric acid resin.•Linseed oil based epoxy resin is an alternative to polyurethane as a cork binder.•Cork bound with linseed oil resin absorbs less solvent than with polyurethane.•Cork bound with linseed oil based resin is more hydrophobic than with polyurethane.•Cork bound with biobased resin has better mechanical properties than polyurethane.